Coexistent sarcoidosis mimics metastasis in a patient with early-stage non-small cell lung cancer: a case report: Coexistent Sarcoidosis and NSCLC - Zhao, Xiang; Cheng, Yuan; Wang, Wei (Sarcoidosis, Vasculitis and Diffuse Lung Diseases, 2024)
Background and aim: Sarcoidosis is a granulomatous disease. Malignant tumors are accompanied rarely by granuloma reactions that mimic metastasis. Methods: We present the case of a patient with possible advanced lung cancer with metastases to the mediastinal lymph nodes and bilateral ilia. Results: Ilium biopsy revealed the presence of sarcoid-like reaction. Bronchoscopy and endobronchial ultrasound revealed an adenocarcinoma in the right upper lung lobe, with a negative mediastinal lymph node. The correct staging of lung cancer was achieved through pathological examination of the surgically removed lung tissues. Two years later, the lung cancer metastasized, and the patient underwent systemic treatment. Conclusions: Coexistent sarcoid-like reaction may mimic metastatic lung cancer. A multidisciplinary approach and sequential diagnostic biopsies can prevent unnecessary surgery or inadequate treatment by distinguishing between coexistent sarcoidosis and metastatic lung cancer.